The legal protection of women from violence : normative gaps in international law - Manjoo, Rashida; Jones, Jackie M. (Abingdon, Oxon : Routledge, 2018)
Violence against women remains one of the most pervasive human rights violations in the world today, and it permeates every society, at every level. Such violence is considered a systemic, widespread and pervasive human rights violation, experienced largely by women because they are women. Yet at the international level, there is a gap in the legal protection of women from violence. There is currently no binding international convention that explicitly prohibits such violence; or calls for its elimination; or, mandates the criminalisation of all forms of violence against women.The book puts forward a strong case that there is a legal gap in international law for the protection of women and girls from violence and that this could be remedied through a new United Nations Convention or alternatively an Optional Protocol to the Convention on the Elimination of all Forms of Discrimination against Women.
The importance of international law and institutions (Jackie Jones) -- Exploring the consequences of the normative gap in legal protections addressing violence against women (David richards and Jillienne Haglund) -- Normative developments on violence against women in the United Nations System (Rashida Manjoo) -- The African human rights system : challenges and potential in addressing violence against women in Africa (Nicholas Wasonga Orago and Maria Nassali) -- The European system : Convention on Human Rights (ECHR) and the Council of Europe Convention on Violence against Women and Domestic Violence (Istanbul Convention) (Jackie Jones) -- Violence against women : normative developments in the Inter-American Human Rights System (Caroline Bettinger-Lopez) -- Closing the normative gap in international law on violence against women : developments, initiatives, and possible options (Rashida Manjoo).
Includes bibliographical references and index.
Keywords: Women -- Violence against; Women -- Crimes against -- Law and legislation; Women -- Legal status, laws, etc; Women (International law).